Evidence of a Cell Surface Role for Hsp90 Complex Proteins Mediating Neuroblast Migration in the Subventricular Zone - Miyakoshi, Leo M.; Marques-Coelho, Diego; De Souza, Luiz E. R.; Lima, Flavia R. S.; Martins, Vilma R.; Zanata, Silvio M.; Hedin-Pereira, Cecilia (Frontiers in Cellular Neuroscience, 2017)
In most mammalian brains, the subventricular zone (SVZ) is a germinative layer that maintains neurogenic activity throughout adulthood. Neuronal precursors arising from this region migrate through the rostral migratory stream (RMS) and reach the olfactory bulbs where they differentiate and integrate into the local circuitry. Recently, studies have shown that heat shock proteins have an important role in cancer cell migration and blocking Hsp90 function was shown to hinder cell migration in the developing cerebellum. In this work, we hypothesize that chaperone complexes may have an important function regulating migration of neuronal precursors from the subventricular zone. Proteins from the Hsp90 complex are present in the postnatal subventricular zone as well as in the RMS. Using an in vitro SVZ explant model, we have demonstrated the expression of Hsp90 and Hop/STI1 by migrating neuroblasts. Treatment with antibodies against Hsp90 and co-chaperone Hop/STI1, as well as Hsp90 and Hsp70 inhibitors hinder neuroblast chain migration. Time-lapse videomicroscopy analysis revealed that cell motility and average migratory speed was decreased after exposure to both antibodies and inhibitors. Antibodies recognizing Hsp90, Hsp70 and Hop/STI1 were found bound to the membranes of cells from primary SVZ cultures and biotinylation assays demonstrated that Hsp70 and Hop/STI1 could be found on the external leaflet of neuroblast membranes. The latter could also be detected in conditioned medium samples obtained from cultivated SVZ cells. Our results suggest that chaperones Hsp90, Hsp70 and co-chaperone Hop/STI1, components of the Hsp90 complex, regulate SVZ neuroblast migration in a concerted manner through an extracellular mechanism. Keywords: neuroblast migration, rostral migratory stream, HSP90, HSP70, Hop/STI1